Effect of Antilymphocyte Serum on Reovirus Infection of Mice - Ida, Shiroh (1971)
Reovirus type 3 infection in mice was investigated, with particular reference to the effect of antilymphocyte serum. With virus inoculation, a characteristic acute disease was manifested in the mice younger than 5 days old but not in mice 7 days old or older. However, a single injection of antilymphocyte serum, which was prepared in rabbits immunized with mouse thymocytes, followed by virus inoculation induced the acute disease in mice 7 days old or older. The latter result suggests that this production of the acute disease may be due to a suppression of the cellular immune mechanism sensitive to antilymphocyte serum.